Kepemilikan Institusional, Kepemilikan Manajerial, dan Risiko Bisnis Terhadap Struktur Modal dengan Ukuran Perusahaan sebagai Moderasi - Nabila, Alfiana Sukma; Yusuf, Muhammad; Prihatni, Rida (Jurnal Akuntansi, Perpajakan dan Auditing, 2024)
This study aims to analyze the effect of institutional ownership, managerial ownership, and business risk on capital structure with company size as a moderating variable. This study uses quantitative methods by taking the population of companies listed on the Indonesia Stock Exchange (IDX) in the property sector. The sample was selected using purposive sampling technique so that a total of 33 property companies were obtained in the period 2020-2022. The data analysis method used is panel data regression analysis and moderated regression analysis (MRA) using the Eviews 12 test tool. The results showed that institutional ownership has a negative and significant effect on capital structure, managerial ownership has no effect on capital structure, business risk has no effect on capital structure. The proven moderation test result is that firm size significantly moderates the relationship between institutional ownership and capital structure.